DAINELLINAE SUBFAM. NOV. (EARLY CARBONIFEROUS FORAMINIFERIDA), REVIEW AND NEW TAXA - Cózar P.; Vachard D. (My University, 2001)
The family Loeblichiidae Cummings already emended by Rauser-Chernousova et al. (1996), is revised and subdivided into three subfamilies: Loeblichiinae Cummings emend., Spinoendothyrinae subfam. nov., Dainellinae subfam. nov. This latter is accurately studied with redescription of the genera: Dainella emend., Lysella emend., Paralysella gen. nov., Bessiella emend. (= Florennella), Paradainella, Bozorgniella gen. nov., Vissarionovella gen. nov. including four species: V. tujmasensis, V. donzellii sp. nov., V. cf. llangollensis and V. sp. nov. The Dainellinae are very important for the biozonation of the interval ranging from latest Tournaisian (Tn3c) to early late Viséan (V3a, V3b?); V. donzellii sp. nov. is probably a marker of the Spanish V3a. From the subfamily Dainellinae arise numerous lineages: Loeblichiinae, Globoendothyrinae, Eoendothyranopsinae, Ozawainellacea, Staffellacea. Therefore its representatives are the ancestors of the Fusulinina from middle Carboniferous to Permian, the missing link between Endothyrina and Fusulinina, after the unsuccessful tentative of the Quasiendothyridae at the end of the Devonian.
Keywords: Carboniferous; Loeblichiidae; Paleozoic::Carboniferous; Палеозой::Каменноугольная